Reproductive strategies and isolation‐by‐demography in a marine clonal plant along an eutrophication gradient. Issue 23 (15th November 2014) - Oliva, Silvia; Romero, Javier; Pérez, Marta; Manent, Pablo; Mascaró, Oriol; Serrão, Ester A.; Coelho, Nelson; Alberto, Filipe
Abstract Genetic diversity in clonal organisms includes two distinct components, (i) the diversity of genotypes or clones (i.e. genotypic richness) in a population and (ii) that of the alleles (i.e. allelic and gene diversity within populations, and differentiation between populations). We investigated how population differentiation and genotypic components are associated across a gradient of eutrophication in a clonal marine plant. To that end, we combined direct measurements of sexual allocation (i.e. flower and seed counts) and genotypic analyses, which are used as an estimator of effective sexual reproduction across multiple generations. Genetic differentiation across sites was also modelled according to a hypothesis here defined as isolation‐by‐demography, in which we use population‐specific factors, genotypic richness and eutrophication that are hypothesized to affect the source‐sink dynamics and thus influence the genetic differentiation between a pair of populations. Eutrophic populations exhibited lower genotypic richness, in agreement with lower direct measurements of sexual allocation and contemporaneous gene flow. Genetic differentiation, while not explained by distance, was best predicted by genotypic richness and habitat quality. A multiple regression model using these two predictors was considered the best model (R2 = 0.43). In this study, the relationship between environment and effective sexual–asexual balance is not simply (linearly) predicted by direct measurements of sexual allocation. Our results indicate that population‐specific factors and the isolation‐by‐demography model should be used more often to understand genetic differentiation.